Individual participant data analysis comparing acute stroke patients with anterior versus posterior circulation dissections - Zhang, Yanan; Zhang, Yang; Fröhlich, Kilian; Mrochen, Anne; Mühlen, Iris; Lang, Stefan; Lehmann, Sophie; Gerner, Stefan T.; Huttner, Hagen B.; Schwab, Stefan; He, Li; Bobinger, Tobias (Clinical Neurology and Neurosurgery, 2024)
Background: Cervical artery dissection (CAD) is a relevant etiology of transient ischemic attacks and strokes. Several trials explored the significance of specific antithrombotic treatments, i.e. oral anticoagulation (OAC) versus antiplatelet treatment (APT), on recurrent ischemic complications and clinical outcomes. As overall incidence rates of complications were low there is still controversy which antithrombotic treatment should be used. However, up to now there has been no systematic investigation among CAD-patients with ischemic stroke specifically comparing clinical course and outcome of patients with anterior versus posterior CAD. Methods: We performed an individual participant data analysis of patients with CAD and ischemic stroke. Over a five-year period we pooled data from three sites (i.e. West China Hospital, Chengdu, China as well as Erlangen and Giessen University Hospitals, Germany) and enrolled patients with CAD-associated ischemic stroke. Patient demographics, clinical and in-hospital measures as well as radiological data were retrieved from institutional databases. Clinical follow-up was over 6 months and included data on recurrent ischemic strokes and hemorrhages as well as clinical functional outcome assessed by the modified Rankin Scale dichotomized into favourable (mRS=0–2) and unfavourable. Results: A total of 203 patients with CAD were included of which n=112 had anterior and n=91 had posterior CAD. Patients with posterior CAD were younger (46.0 vs. 41.0 y; p<0.001) than patients with anterior CAD and showed less often arterial hypertension. (42.0 % vs. 28.6 %; p<0.048). Antithrombotic treatment with APT and OAC was similarily distributed among patients with anterior and posterior CAD and not significantly differently related to ischemic or hemorrhagic complications during follow-up (all p=n.s.). Main difference between Chinese and German patients were mode of antithrombotic treatment consisting predominantly of APT in China compared to OAC in Germany. Functional outcome overall was good, yet worse in patients with anterior CAD compared to posterior CAD (80.2 % favorable in anterior CAD vs. 92.2 % in posterior CAD (p=0.014). Conclusion: This study provides evidence that anterior and posterior CAD show baseline imbalances regarding age and comorbidity which may affect clinical outcome. There are no signals of superiority or harm of any specific mode of antithrombotic treatment nor relevant discrepancies in clinical outcome among Chinese and German CAD-associated stroke patients.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Acute ischemic stroke; Antiplatelet treatment; Cervical artery dissections; Clinical outcome; Oral anticoagulation